An assessment of the impact of declining water quality on tourism : a case study of Loskop Dam, Mpumalanga, South Africa - Makwela, Tshegofatso Rahab (My University, 2022)
Various studies have indicated problems of water pollution in South Africa, with some of them highlighting the high concentrations of chemical pollutants in the Loskop Dam. These reports show how pollution in the dam has affected aquatic life and poses a health risk. However, limited studies have been conducted on the impact of declining water quality on tourism in Loskop Dam. These studies focus more on the ecological aspect of the dam. Therefore, the main objective of the current study is to explore how tourism is affected by the declining water quality in Loskop Dam by examining the impacts of water pollution on the tourism sector linked to Loskop Dam and associated socio-economic effects. A questionnaire-based survey was conducted to collect information from small and medium-scale enterprises (SMEs) employees and freshwater tourists, and interviews were conducted with SME managers to get more information on tourism activities, water pollution in Loskop Dam, as well as information on the impacts of decreased water quality. The outcome is that a decrease in water quality affects tourism negatively, inclusive of recreational activities, business operations, and subsequently having a negative social and economic impact on Loskop visitors and employees.
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2022
Keywords: Pollutants; Water quality; Tourism; Pollution; Loskop dam; Water-supply; Water-supply -- South Africa -- Mpumalanga; Water quality -- South Africa -- Mpumalanga; Water -- Pollution; Tourism -- South Africa -- Mpumalanga